Comparison of the Results of Chest X-ray Versus Chest Computed Tomography in Patients With Stab Wound Chest Injuries - Ramin Ebrahimian Jektaji; Mahta Moghaddam Ahmadi; Seyyed Mahdi Zia Ziabari; Sahar Bani Hashemi; Moein Moghaddam Ahmadi (Disease and Diagnosis)
Background: Injuries after normal chest X-ray (CXR) and chest computed tomography (CCT) have been observed in patients with thoracic stab wounds, which can increase the rate of subsequent complications in such patients. This study aimed to compare the results of CXR versus CCT in patients with stab wound chest injuries. Materials and Method: Overall, 371 patients with stab wound chest trauma who were referred to Poursina Hospital, Rasht, Iran, were included in this cross-sectional study. Demographical data, clinical characteristics, and all patients’ CXR and CCT results were recorded, and all data were analyzed using SPSS version 24 and MedCal version 19.0.5, with a significant level set at 0.05. Results: According to the findings, the patients’ mean age was 28.54±9.43 years, and 359 of them were men (96.8%). About 266, 24, 15, and 21 patients had normal pneumothorax, hemothorax, and hemopneumothorax results for primary CXR, respectively, and 118 patients had normal results for the second CXR. The area under the curve (AUC) for CXR was 0.75, with sensitivity and specificity of 0.50 and 0.100, respectively. The specificity of the diagnostic method was 100%, while the AUC represented no statistically significant association (P>0.05). Conclusion: The results of the present study demonstrated that CCT was more sensitive than CXR in diagnosing injuries in patients with stab wound chest injuries.